Need Analysis of Digital Microlearning Materials with Scaffolding for Generation Z Pre-Service Teachers in Islamic Primary Education - Rizki Amelia; Agus Mukti Wibowo; Sigit Priatmoko; Wiku Aji Sugiri; Galih Puji Mulyoto (UIN Siber Syekh Nurjati Cirebon, 2025)
AbstractThis study aims to analyze the need for digital teaching materials based on microlearning with scaffolding to support Generation Z pre-service elementary school teachers. The research method used was a quantitative descriptive survey, with data collected through an online questionnaire filled out by 216 Generation Z students, pre-service teachers in the Madrasah Ibtidaiyah Education Study Program (PGMI) at UIN Maulana Malik Ibrahim Malang, Indonesia. The study results indicate that most students have adequate access to digital devices and the internet and a strong preference for the blended learning method. Students also prefer short and interactive video-based teaching materials, which support flexibility in arranging time and place of study. These findings emphasize the importance of developing microlearning teaching materials for the characteristics of the digital native generation. Scaffolding is identified as a supportive approach in compiling microlearning-based teaching materials. Therefore, it can provide gradual guidance that helps students understand the material more deeply. All in all, this study provides insight into developing teaching materials that are adaptive, effective, and in line with learning needs in the digital era.Keywords: microlearning, scaffolding, Gen Z.AbstrakPenelitian ini bertujuan untuk menganalisis kebutuhan bahan ajar digital berbasis microlearning dengan scaffolding untuk mendukung calon guru SD Generasi Z. Metode penelitian yang digunakan adalah survei deskriptif kuantitatif, dengan data dikumpulkan melalui kuesioner daring yang diisi oleh 216 mahasiswa Generasi Z calon guru Program Studi Pendidikan Guru Madrasah Ibtidaiyah UIN Maulana Malik Ibrahim Malang, Indonesia. Hasil penelitian menunjukkan bahwa sebagian besar mahasiswa memiliki akses yang memadai terhadap perangkat digital dan internet serta preferensi yang kuat terhadap metode blended learning. Mahasiswa juga lebih menyukai bahan ajar berbasis video yang singkat dan interaktif, yang mendukung fleksibilitas dalam mengatur waktu dan tempat belajar. Temuan ini menekankan pentingnya pengembangan bahan ajar microlearning bagi karakteristik generasi digital native. Scaffolding diidentifikasi sebagai pendekatan yang suportif dalam menyusun bahan ajar berbasis microlearning. Dengan demikian, scaffolding dapat memberikan bimbingan bertahap yang membantu mahasiswa memahami materi lebih dalam. Secara keseluruhan, penelitian ini memberikan wawasan tentang pengembangan bahan ajar yang adaptif, efektif, dan sejalan dengan kebutuhan pembelajaran di era digital.Kata kunci: pembelajaran mikro, scaffolding, Gen Z.